Biochemical studies of the multicopper oxidase (small laccase) from Streptomyces coelicolor using bioactive phytochemicals and site‐directed mutagenesis. Issue 5 (1st July 2013) - Sherif, Mohammed; Waung, Debbie; Korbeci, Bihter; Mavisakalyan, Valentina; Flick, Robert; Brown, Greg; Abou‐Zaid, Mamdouh; Yakunin, Alexander F.; Master, Emma R.
Summary: Multicopper oxidases can act on a broad spectrum of phenolic and non‐phenolic compounds. These enzymes include laccases, which are widely distributed in plants and fungi, and were more recently identified in bacteria. Here, we present the results of biochemical and mutational studies of small laccase (SLAC), a multicopper oxidase from Streptomyces coelicolor (SCO6712). In addition to typical laccase substrates, SLAC was tested using phenolic compounds that exhibit antioxidant activity. SLAC showed oxidase activity against 12 of 23 substrates tested, including caffeic acid, ferulic acid, resveratrol, quercetin, morin, kaempferol and myricetin. The kinetic parameters of SLAC were determined for 2, 2′‐azino‐bis(3‐ethylbenzthiazoline‐6‐sulphonic acid), 2, 6‐dimethoxyphenol, quercetin, morin and myricetin, and maximum reaction rates were observed with myricetin, where kcat and Km values at 60°C were 8.1 (± 0.8) s −1 and 0.9 (± 0.3) mM respectively. SLAC had a broad pH optimum for activity (between pH 4 and 8) and temperature optimum at 60–70°C. It demonstrated remarkable thermostability with a half‐life of over 10 h at 80°C and over 7 h at 90°C. Site‐directed mutagenesis revealed 17 amino acid residues important for SLAC activity including the 10 His residues involved in copper coordination. Most notably, the Y229A and Y230A mutant proteins showed over 10‐fold increase in activity compared with the wild‐type SLAC, which was correlated to higher copper incorporation, while kinetic analyses with S929A predicts localization of this residue near the meta ‐position of aromatic substrates. Abstract : Activity of SLAC and the S292A variant on a broad range of compounds, including bioactive phytochemicals.